Vpliv sprememb ZPP na uveljavljanje pravic pred delovnimi in socialnimi sodišči - Kogej Dmitrovič, Biserka (Delavci in delodajalci, 2017)
The procedure of the labour and social disputes is regulated by the Labour and Social Court Act (ZDSS-1); in case there are no relevant provisions in the mentioned act, the provisions of the CPA (Civil Procedures Act) are applied. This year, an amendment to the CPA was adopted which - apart from the provisions already in use - will become effective as of 14 September 2017. By the amendment to the CPA-E, certain provisions of the ZDSS-1 were repealed, yet the majority of the provisions of the amendment to the CPA-E applies also to proceedings before the Labour and Social Court. This paper presents an overview of the changes that affect the proceedings before the Labour and Social Courts.
Keywords: delovna sodišča; delovni spor; pravdni postopek; socialna sodišča; socialni spor